Laser Induced Dissociation Control of $H_2^+$ and $H_3^{2+}$ (Journal of Atomic and Molecular Sciences, 2017)
Laser induced dissociation control of the symmetric diatomic molecular ion $H_2^+$ and the triatomicmolecular ion $H_3^{2+}$ is discussed. The simulation results demonstrate that a long-wavelength terahertz or mid-infraredlaser pulse can be used to control the electrons of the dissociative states after the excitation of anultrashort ultraviolet (UV) laser pulse. For $H_2^+,$ there exists an effective time, which increases with increasingpulse duration of the UV laser pulse, for controlling the molecular dissociation. For the electrons of the $1sσ_g$ state, they move along the polarization direction of the dissociation control electric field. In contrast, for theelectrons of the $2pσ_u$ state, they move in the opposite direction to that of the electric force. And for thetriatomic molecule $H_3^{2+}$, the electron dissociation control can also be realized by changing the centralwavelength of the exciting UV pulse.